Training of Future Psychologists: Providing Sustainable Rehabilitation Services to War Victims - Vasylenko, Olena; Komar, Taisiia; Pavlyuk, Yevgen; Beregova, Natalia; Dzhyhun, Liudmyla; Ihumnova, Olha; Havrylkevych, Viacheslav (European Journal of Sustainable Development, 2024)
The paper examines the problem of training future psychologists to provide rehabilitation services to war victims. It has been found that the psychological rehabilitation of war victims involves the work of psychologists to accelerate their psychological adaptation and prevent psychological complications that provoke the results of mental traumas associated with the provision of leaving home, work, usual comfortable life, etc. Therefore, psychologists must be ready to work with such persons and have a high level of professional competence. All this ensures effective professional training of future psychologists in institutions of higher education and the development of components of their readiness to provide rehabilitation services to war victims. We have found that these readiness components include: motivational, cognitive, operational and personal. The results of the diagnosis of the readiness components of psychology students to provide rehabilitation services to war victims have shown that, in addition to the personal component of readiness, all other components are developed at a sufficient level and this is due to the need to develop measures that are able to contribute to improving the level of training of future psychologists for psychological rehabilitation activities. Key words: psychology students; psychological rehabilitation; war victims; readiness for professional activity